A contribution to the study of the tetractinellid sponge Thenea muricata with special consideration of its importance in the bionomics of the Adriatic sea. - Gamulin-Brida, H. (Thalassia Jugoslavica, 1969)
According to K. Babic (1915, 1917 and 1928) the tetractinellid sponge Thenea muricata occurs in the Adriatic in the form of the subspecies Thenea muricata schmidti Sollas; we have reached the conclusion, based on studies in the characteristics of specimen from the Adriatic and those from the Mediterranean that the species found in the Adriatic is also Thenea muricata (Bowerbank) Gray. The species is closely connected with the special facies of clayey-loamy sediment and can be considered as an indicator of the biocoenose Nephrops norvegicus - Thenea muricata which is very widely distributed in the Adriatic. In supplementing Babic's (1917) consummate study of the species, we wish to emphasize the role of the bundles of megasclerae which help the species to maintain itself on muddy bottoms and to adapt to life on the biotope. 'The sponge Thenea muricata from the Adriatic sea was studied with special consideration of the spicules. X-ray powder method diagrams of the spicules show them to contain Si02 in amorphous state or in minute, irregularly distributed crystals.